Dispersion of the bagworms Pteroma pendula and Metisa plana in oil palm - Ho Cheng Tuck, Ibrahim Yusof, Khoo Khay Chong, (N/A, 2012)
Dispersion of the bagworms Pteroma pendula and Metisa plana in oil palm by Ho Cheng Tuck, Ibrahim Yusof, Khoo Khay Chong,